APLIKASI KONSELING ISLAMI PADA ANAK USIA DINI - Tarsono Tarsono (Psympathic : Jurnal Ilmiah Psikologi, 2012)
Young learner education aims to increase belief, personality, and daily worship. This research focus on parents and teachers roles increasing belief of children in kindergarten. Islamic counseling in kindergarten is not spesifically programmed since it is still integrated with religion program. Applying moral and religious values is considered  important including 1) basic belief to Allah SWT, 2) basic personality, and 3) children habit in daily worship. Result shows that some children in kindergarten have not applied daily worship appropriately. Parents support are asking praying together, inviting religion teacher, and providing media. Teacher can make schedule for praying together and making media of praying.